SECONDARY METABOLITES FROM MANGROVE ENDOPHYTES: THEIR SIGNIFICANCE AGAINST CARBAPENEMASE RESISTANT ENTEROBACTERIACEAE – A REVIEW - R.NATHIYA; GAYATHRI MAHALINGAM (International Journal of Pharma and Bio Sciences, 2016)
The emergence of Carbapenem-resistant Enterobacteriaceae (CRE) causes high mortality rate and is one of the most important medical issue worldwide including developing countries. The resistant pattern of CRE seems towards lactam antibiotics, including the third generation of cephalosporin except aztreonam and clavulanic acid due to the presence of resistance pattern in mobile genes. Consequently, we are in the urge to develop a new therapeutic drug against CRE to reduce the high mortality rate. Endophytes play an important role in developing a novel drug for various diseases. Recently, many researchers are working on endophytic fungi against multi-drug resistant strains to develop the novel drug. Therefore, the present review focuses on